Detection of Giardia duodenalis and Cryptosporidium spp. in water and fresh vegetables - Silva, Maria Madalena Pires de Mendonça (2021)
Giardia duodenalis and Cryptosporidium spp. represent a major cause of diarrheal disease in humans and animals worldwide, and the main waterborne and foodborne diseases caused by protozoa. Cryptosporidium oocysts and Giardia cysts are shed in the feces of the infected host and are transmitted either directly, by contact with infected feces, or indirectly, through ingestion of contaminated water or food. Furthermore, (oo)cysts can be found in aquatic and terrestrial environments and are very resistant to harsh environmental conditions and chemical and physical disinfectants. In the latest years, significant disease outbreaks due to Giardia spp. and Cryptosporidium spp., caused by the use of contaminated water and the consumption of fresh vegetables, have raised severe concerns about waterborne and foodborne zoonotic pathogens, and about the current methods used for monitoring and treatment. This study aimed to detect emerging protozoa, Giardia duodenalis and Cryptosporidium spp., in water and vegetable samples considering the global impact on public health. The detection of these parasitic protozoa occurred according to Method 1623.1- Cryptosporidium and Giardia in Water by filtration/immunomagnetic separation/immunofluorescence assay microscopy. The samples were observed in a fluorescence microscope, where it was possible to detect several Cryptosporidium spp. oocysts and Giardia duodenalis cysts in water and vegetables. To confirm the presence of these oo(cysts), molecular techniques such as DNA extraction, PCR, DNA purification, and sequencing were used. PCR results using the ssu rRNA gene were negative for both Cryptosporidium spp. as for Giardia duodenalis probably due to the low number of oo(cysts) in each sample. However, PCR with the β-giardin gene of Giardia duodenalis was found to be positive in one of the water samples. Sequencing confirmed this positive result.